PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL UNTUK EDUKASI STOP BULLYING PADA SISWA SD SESE - Widyawati Widyawati; Yolpi Wukusenggo; Asman Asman; Ria Ramadhan; Sarah Sarah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
This community service aims to develop digital learning media as an educational tool to stop bullying among elementary school students. The increasing issue of bullying in the school environment has a negative impact on students' psychological and academic development. This community service uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of the community service are students in grades I-VI at Sese Elementary School. Data were collected through observation, interviews, questionnaires, and product trials. The results of the community service show that the digital learning media developed, in the form of an animation-based interactive application, is considered very feasible and effective by media and material experts, and received a positive response from students and teachers. This media has succeeded in increasing students' understanding of the types of bullying, its impacts, and how to prevent and report bullying. Thus, this digital learning media can be an innovative alternative in supporting the formation of empathetic and anti-bullying student characters from an early age.